Solar driven hydrogen generation for a fuel cell power plant - Amoo, Akinlawon Olubukunmi (My University, 2012)
There are a number of ways to produce hydrogen using solar energy as the primary source. Water electrolysis, which uses solar electrical energy, is the rapidly available process. Hydrogen can be produced by using solar electric energy from photovoltaic (PV) modules for the electrolysis of water without emitting carbon dioxide or requiring fossil fuels. Solar hydrogen energy systems are considered one of the cleanest hydrogen production technologies, where the hydrogen is obtained from sunlight by directly connecting the photovoltaic modules to the hydrogen generator. This dissertation presents a designed solar photovoltaic electrolyser hydrogen production and storage system for various applications such as in the power generation and telecommunications industries. Various experiments were performed on the designed system to ensure its reliability and conformity with theoretical findings. The purity of the generated hydrogen was determined. The relationship between the amount of solar irradiance reaching the surface of the PV panel, the PV panel surface temperature, the PV panel tilt angle and the maximum power point voltage and current of the PV panel array were also considered. The effect of dust on the panel voltage and current outputs was also determined. Finally, the factors to consider when designing a solar photovoltaic electrolyser hydrogen system (based on this study) were enumerated.
Thesis. (M. Tech. (Dept. Electronic Engineering, Faculty of Engineering and Technology))--Vaal University of Technology, 2011.
Keywords: Hydrogen; Solar energy; Water electrolysis; Solar electrical energy; Solar hydrogen energy systems; Solar photovoltaic electrolyser hydrogen; 621.47; Solar energy; Hydrogen; Photovoltaic power systems